1999
DOI: 10.1128/jvi.73.1.110-119.1999
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of Baculovirus IE-1 and Two DNA-Binding Proteins, DBP and LEF-3, to Viral Replication Factories

Abstract: We have recently identified a DNA-binding protein (DBP) from the baculovirus Bombyx mori nucleopolyhedrovirus (BmNPV) which can destabilize double-stranded DNA (V. S. Mikhailov, A. L. Mikhailova, M. Iwanaga, S. Gomi, and S. Maeda, J. Virol. 72:3107–3116, 1998). DBP was found to be an early gene product that was not present in budded or occlusion-derived virions. In order to characterize the localization of DBP during viral replication, BmNPV-infected BmN cells were examined by immunostaining and confocal micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(34 citation statements)
references
References 46 publications
2
31
0
1
Order By: Relevance
“…Similar to BmN cells infected with BmNPV (Okano et al, 1999), DBP appeared to be about twice as abundant as LEF-3 in Sf9 cells infected with AcMNPV. The Sf9 cells at 20 hpi contained approximately 3 × 10 7 molecules of DBP and 1.5 × 10 7 molecules of LEF-3.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Similar to BmN cells infected with BmNPV (Okano et al, 1999), DBP appeared to be about twice as abundant as LEF-3 in Sf9 cells infected with AcMNPV. The Sf9 cells at 20 hpi contained approximately 3 × 10 7 molecules of DBP and 1.5 × 10 7 molecules of LEF-3.…”
Section: Discussionmentioning
confidence: 75%
“…Firstly, DBP appeared to be less abundant in Sf9 cells infected with AcMNPV than in BmN cells infected with BmNPV. A quantitative Western blot analysis performed as previously described (Mikhailov et al, 1998) showed that an average Sf9 cell infected with AcMNPV contains approximately 3 × 10 7 molecules of DBP at 20 hpi, significantly lower than the amount of DBP (7 × 10 7 molecules) in the BmN cell infected with BmNPV at 14 hpi (Okano et al, 1999). Secondly, the treatment with high salt released only a minor fraction of DBP from the nuclei.…”
Section: Purification Of Acmnpv Dbpmentioning
confidence: 85%
See 2 more Smart Citations
“…Till date no effective protective method has been developed against WSSV infection, because WSSV are easily spread in the environment of shrimp farms (soil, water, and other materials used for the farm maintenance) [11]. Therefore early detection of WSSV is very useful to shrimp industries.…”
Section: Introductionmentioning
confidence: 99%